Testing, numerical modelling and design of Q690 high strength steel welded T-section stub columns. (15th May 2022) - Liu, Jun-zhi; Chen, Shuxian; Chan, Tak-Ming
Highlights: 16 Experimental tests have been performed. Numerical models for HSS welded T-section have been developed. Extensive parametric studies have been carried out. Design methods from design codes, and from DSM and CSM have been assessed. Abstract: This paper presents a comprehensive experimental and numerical investigation into the material properties and stub column behaviour of Q690 high strength steel (HSS) welded T-sections. A total of 16 concentrically loaded stub column tests were performed. The Q690 HSS welded T-sections were fabricated from 6 mm and 10 mm thick plates, delivered in quenched and tempered (QT) conditions by means of gas metal arc welding (GMAW). Material properties measurements were carried out on the coupon specimens taken from the parent plates. Initial local geometric imperfection measurements were conducted. In conjunction with experimental tests, finite element (FE) models were developed to replicate the test results and failure modes. Afterwards, the validated FE models were adopted to conduct parametric studies to supplement the experimental data by generating further structural performance data covering a broader range of cross-section slenderness. Cross-section slenderness limits set out in design codes such as EN 1993-1-12, ANSI/AISC 360-16, AS 4100 and design methods of DSM as well as CSM were evaluated against the experimental and numerical data. It was found that the current limits are generally accurate and safe in three design codes and the cross-section slenderness of DSM is accurate and comparably conservative. Cross-section capacities predictions obtained from EN 1993-1-12, ANSI/AISC 360-16, AS 4100, DSM and CSM were also compared with the tests and numerical results. It is shown that the established local buckling design provisions in EN 1993-1-12 and ANSI/AISC 360-16 result in more precise and consistent predictions compared with AS 4100, DSM and CSM.